Analysis of Intra-Aortic Balloon Performance in Open-Heart Surgery - Wajeeh, Zainab A.; Hamandi, Sadiq J.; Alobaidi, Wisam S.; Tedy, Georges B. (Al-Nahrain Journal for Engineering Sciences, 2023)
A failing heart can be supported in several ways, including cardiopulmonary bypass pumps (CPB), extracorporeal membrane oxygenators (ECMOs), and other types of auxiliary heart pumps. The intra-aortic-balloon-pump (IABP) is one technique of internal counter-pulsation that supports maintaining the circulatory system It continues to be used as a vascular support device to critically unwell cardiac patients. Many recent studies have focused on the problems of the (IABP) in open-heart surgery, while other researchers concentrated on the positioning and size of the balloon, some of them studied the timing of the balloon's inflation and deflation. this paper has reviewed a brief Introduction, the basic principles of the balloon, how to trigger the balloon pump as well as the use of IABP in Coronary Artery Bypass Graft (CABG), balloon mistiming of inflation and deflation, balloon timing usage within open-heart surgery and finally a balloon position and sizing.